Implementasi Indikator Pendeteksi Stophunt Pada Pasar Mata Uang Dengan Menggunakan Expert Advisor - Alex Christopher; Agustinus Noertjahyana; Alexander Setiawan (Jurnal Infra, 2019)
Trading activity in forex market is one of promising business opportunity that gives decent profit and freedom to it’s doer without providing big capital or physical office. However, the majority of people lose money because there’s a market manipulation that retail trader don’t notice. That’s why there’s needs to form a trading system, indicator, and expert advisor that could follow the movement of market manipulation. Trading system, indicator, and expert advisor follows the market structure that’s been made by market maker to induce retail trader to follow a fake market movement trend that ends with immediate reversal of the direction of the market price movement. The result of the testing provides a forex indicator that can detect a potential pattern that’s been used by market maker to reverse the market price direction, an expert advisor that can immediately gives notification of potential market manipulation and trading system that follows the movement of market manipulation with minimal risk.